HISTOLOGY SLIDE QUALITY COMPARATIVE STUDY; IMPREGNATION AND EMBEDDING USING BEESWAX AND PARAFFIN - Dewi, Hasna; Quzwain, Fairuz; Wulansari, Nadia (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2022)
ABSTRACT Background: Paraffin is the most popular infiltration and embedding medium in histopathology laboratories to date. It is a white or colorless soft solid derived from petroleum, coal or oil shale. Its limitations and calls to return to nature for better sustainability and safety, prompting the search for alternative materials to replace paraffin. The aim of this study is to compare paraffin that is used as routine embedding media and beeswax as alternative in impregnation and embedding of various tissues. Methods: Ten tissue specimens were impregnated and embedded in beeswax and parafiin. After manual processing, all sections were stained with Hematoxylin Eosin to compare the effect of beeswax and paraffin based on the features of the integrity of the section, uniformity of the staining which includes nuclear details, cytoplasmic details, and background staining. Result: Beeswax showed well impregnation and embedding of the tissues as well as the preservation of the nuclear details, good cytoplasmic appearance, good tissue architecture and no bad effect on staining characteristics of the tissue. Conclusion: Beeswax could be an alternative to paraffin. Further research on the resistance of the block during storage and whether it affects other tests such as immunohistochemistry needs to be done. Keywords: Beeswax, Embedding, Impregnation, Paraffin ABSTRAK Pendahuluan: Parafin merupakan media infiltrasi dan embedding yang paling populer digunakan laboratorium histopatologi hingga saat ini dalam membuat preparat histologi. Parafin merupakan lilin putih tidak berwarna yang berasal dari minyak bumi atau batu bara. Keterbatasannya dan seruan untuk kembali ke alam demi keberlanjutan dan keamanan yang lebih baik, mendorong pencarian bahan alternatif untuk menggantikan parafin. Tujuan dari penelitian ini adalah untuk membandingkan parafin yang digunakan sebagai media tanam rutin dan lilin lebah sebagai alternatif dalam impregnasi dan embedding berbagai jaringan. Metode: Sepuluh spesimen jaringan dibuat menjadi preparat histologi, ditanam dalam lilin lebah dan parafiin. Setelah proses manual, semua preparat diwarnai dengan Hematoxylin Eosin untuk membandingkan efek lilin lebah dan parafin berdasarkan fitur integritas bagian, keseragaman pewarnaan yang meliputi detail inti, detail sitoplasma, dan pewarnaan latar belakang preparat. Hasil: Beeswax menunjukkan impregnasi dan embedding jaringan yang baik serta pelestarian detail inti, penampilan sitoplasma yang baik, arsitektur jaringan yang baik dan tidak ada efek buruk pada karakteristik pewarnaan jaringan. Kesimpulan: Lilin lebah bisa menjadi alternatif pengganti parafin. Penelitian lebih lanjut tentang ketahanan blok selama penyimpanan dan apakah itu mempengaruhi tes lain seperti imunohistokimia perlu dilakukan. Kata kunci: Beeswax, Embedding, Impregnasi, Parafin